Symmetric Pseudoathetosis of Hands and Feet: A Rare Manifestation of Subacute Combined Cord Degeneration With Life‐Threatening Thromboembolic Risk - Siddiqui, Ramsha; Canenguez, Johanna; Thatikonda, Nithisha; Elaneem, Awab; Rodriguez, Fernandez Jorge (Case reports in neurological medicine, 2025)
Vitamin B12 deficiency can cause subacute combined degeneration (SACD) by disrupting myelin synthesis, leading to spinal cord degeneration. We present a unique case of SACD featuring symmetrical pseudoathetosis characterized by involuntary, slow, and writhing movements resulting from proprioceptive sensory impairment, which disrupts the brain’s ability to accurately perceive limb position and movement and pulmonary embolism due to elevated homocysteine levels. A 34‐year‐old male presented with chest pain, generalized weakness, and numbness in his hands and feet. Two months prior, he experienced sharp chest pain, followed by progressive numbness and weakness in his upper and lower extremities. Neurological examination revealed no nuchal stiffness, normal cranial nerve function, and impaired light touch and vibration sensation in the lower extremities. Tremulousness in the hands and feet, suggestive of pseudoathetosis, had been present for 6 months. Laboratory tests confirmed severe vitamin B12 deficiency (< 159 pg/mL), elevated homocysteine, and pancytopenia. MRI of the spine showed hyperintense signals consistent with SACD, and a chest CT revealed a large saddle pulmonary embolus. Pernicious anemia was confirmed as the cause of vitamin B12 deficiency. The patient was treated with intravenous vitamin B12, leading to significant neurological improvement. This case is the first documented instance of SACD presenting with symmetrical pseudoathetosis in all four extremities. Recognizing this rare clinical sign is essential, as it can guide early diagnosis and treatment. In addition, hyperhomocysteinemia associated with vitamin B12 deficiency is a significant risk factor for thromboembolism, underscoring the need for screening in patients with unexplained thrombotic events.